2021
DOI: 10.2147/clep.s268556
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Factors, Use of Exogenous Hormones, and Pancreatic Cancer Incidence: The Norwegian Women and Cancer Study

Abstract: Introduction The incidence of pancreatic cancer is increasing worldwide and characterized by a particularly low survival rate. Studies have reported weak and inconsistent evidence for associations among reproductive factors, use of exogenous hormones, and pancreatic cancer incidence in women. Purpose To investigate relationships between reproductive factors, exogenous hormones, and the rate of pancreatic cancer incidence in a large population-based prospective cohort of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Research on the association between reproductive factors and the risk of PDAC has shown heterogenous results. Some studies have suggested that high parity [ 17 , 18 ], having had two children [ 19 ], and a cumulative breastfeeding duration of over 24 months [ 20 ] are associated with a decreased risk of pancreatic cancer. However, subsequent large cohort studies [ 21 , 22 ] have failed to identify a strong association between reproductive factors and pancreatic cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the association between reproductive factors and the risk of PDAC has shown heterogenous results. Some studies have suggested that high parity [ 17 , 18 ], having had two children [ 19 ], and a cumulative breastfeeding duration of over 24 months [ 20 ] are associated with a decreased risk of pancreatic cancer. However, subsequent large cohort studies [ 21 , 22 ] have failed to identify a strong association between reproductive factors and pancreatic cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of breastfeeding in influencing pancreatic cancer risk is uncertain. The Norwegian Women and Cancer study reported an inverse linear relationship between cumulative breastfeeding duration and pancreatic cancer incidence [ 26 ], although no significant associations were found in a study in Japan [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many observational studies investigated the association between age at rst birth and breast cancer risk [11,12], but these results are inconsistent. Moreover, meta-analysis shows age at rst birth was associated with lung cancer risk, pancreatic cancer risk [13,14], and has no signi cant association with liver cancer [15]. Nevertheless, some of the results are inexact and the underlying mechanism needs further investigation.…”
Section: Introductionmentioning
confidence: 99%